1981
DOI: 10.1177/030098588101800410
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondrosis in Feedlot Cattle

Abstract: Abstract. Beginning in summer 1977 and continuing through four consecutive seasons, we examined lame limb joints from 106 partially fattened cattle and 28,235 pairs of occipital condyles from fully fattened cattle for osteochondrosis. Of the 106 lame cattle, nine (8.5%) had characteristic lesions, usually in their stifle joints, and of the 28,235 atlanto-occipital joints, 1063 (3.8%) had lesions on their condyles.Slices of affected articular cartilage and subjacent bone were studied radiographically and histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0
7

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 2 publications
(3 reference statements)
3
23
0
7
Order By: Relevance
“…40,54 Alternatively, bone cysts have been observed in association with osteochondrosis lesions in central, weightbearing regions of the epiphyses in large animal species such as the horse 40,43 and ox. 20,39 In horses, there are 2 main hypotheses for the pathogenesis of bone cysts following osteochondrosis. First, it has been proposed that an OCD fissure may permit influx of pressurized synovial fluid into epiphyseal bone.…”
mentioning
confidence: 99%
“…40,54 Alternatively, bone cysts have been observed in association with osteochondrosis lesions in central, weightbearing regions of the epiphyses in large animal species such as the horse 40,43 and ox. 20,39 In horses, there are 2 main hypotheses for the pathogenesis of bone cysts following osteochondrosis. First, it has been proposed that an OCD fissure may permit influx of pressurized synovial fluid into epiphyseal bone.…”
mentioning
confidence: 99%
“…formation of cartilaginous flaps (osteochondrosis dissecans), subchondral marrow fibrosis or cyst formation, and sclerosis of subchondral bone have been described in cattle from ages 12 to 19 months, 5,9 No information exists about dyschondroplasia in younger calves or about the histopathologic appearance of early bovine lesions. In pigs, however, early lesions in the joint cartilage are described as focal areas of chondrolysis in the growth cartilage with or without thickening ofthe cartilage extending into the subchondral bone.…”
mentioning
confidence: 99%
“…20 Review of the pedigrees of the calves reported here did not reveal relationships among their lineages, and DIJ lesions were not reported in any of their offspring. A congenital or developmental malformation, such as joint dysplasia or osteochondrosis, that subsequently induces degenerative joint disease was suspected.…”
Section: Discussionmentioning
confidence: 70%